2017
DOI: 10.1177/0954406217736079
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic pull-in analysis of a nonuniform micro-resonator undergoing large elastic deflection

Abstract: Pull-in analysis of an electrostatically actuated nonuniform micro-resonator under large elastic deflection has been investigated with a focus on qualitative analysis to understand the essence of nonuniform cross-section on the determination of pull-in voltage. Here, a microcantilever beam with nonuniform cross-section has been adopted to develop a mathematical model considering the important features such as structural nonlinearities, nonlinear electrostatic distribution, and linear viscous effect. The indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Samaali and Najar [ 43 ] proposed a double-beam RF switch, and the study showed that the pull-in voltage of the double-beam structure was 23% lower than that of the general structure. Prasanth et al [ 44 ] designed structures with non-uniform shape and found that the pull-in voltage increased as the taper degree increased. Almitani et al [ 45 ], Abdelrahman et al [ 46 ], and Eltaher et al [ 47 48 ] proposed a perforated-beam structure, based on cantilever and bridge structures.…”
Section: Reviewmentioning
confidence: 99%
“…Samaali and Najar [ 43 ] proposed a double-beam RF switch, and the study showed that the pull-in voltage of the double-beam structure was 23% lower than that of the general structure. Prasanth et al [ 44 ] designed structures with non-uniform shape and found that the pull-in voltage increased as the taper degree increased. Almitani et al [ 45 ], Abdelrahman et al [ 46 ], and Eltaher et al [ 47 48 ] proposed a perforated-beam structure, based on cantilever and bridge structures.…”
Section: Reviewmentioning
confidence: 99%
“…Effect of various controller and changing coefficients of quadratic controller is presented using frequency analysis curves. Prasanth C. [21] did the quantitative analysis of pull in voltage for electrostatically actuated non-uniform microcantilever MEMS resonator. Also the results are compared through simulation.…”
Section: Functional Related Workmentioning
confidence: 99%
“…NEMS/MEMS devices have huge applications such as micro/Nano-switches, sensors, actuators, atomic force microscopes, micro-mirrors, Nano-transistors, Nano-tweezers, etc. 1822 These structures are composed of a movable electrode and a fixed substrate (ground electrode) and there is a specified initial gap between them. Furthermore, a voltage crosses throughout the circuit connecting these electrodes.…”
Section: Introductionmentioning
confidence: 99%